دور الجمعيات الخيرية الإسلامية الكويتية في التخفيف من الآثار الاقتصادية لجائحة كوفيد-19 على المستوى المحلي والإقليمي: دراسة استقرائية تحليلية: (The Role of Kuwaiti Islamic Charitable Organizations in Mitigating the Economic Impacts of the COVID-19 Pandemic at the Local and Regional Levels: An Analytical Inductive Study) - (Mousa S N Gh Alharbi), موسى سلامة نافع غتر الحربي; (Asmuliadi Lubis), أسموليادي لوبيس; (Mohd Abd Wahab Fatoni Bin Mohd Balwi), محمد عبد الوهاب فتوني بن محمد البلوي (At-Tajdid - Intellectual Refereed Journal, 2025)
This research addresses a highly important topic concerning the role of Kuwaiti Islamic charitable organizations in mitigating the economic impacts of the COVID-19 pandemic at both the local and regional levels. This role is considered pivotal in strengthening social and economic response efforts. The study demonstrates that charitable organizations in Kuwait were highly effective in providing the necessary support and assistance, which contributed to alleviating the effects of the pandemic on affected groups. The study aims to achieve several key objectives, including highlighting the efforts exerted by charitable organizations in Kuwait during the COVID-19 pandemic and exploring the challenges and difficulties they faced. The findings indicate that these organizations did not limit their efforts to providing urgent aid, but also worked to raise community awareness and support small-scale projects, which helped reduce the economic burdens on affected families. The research clearly shows that charitable organizations contributed to strengthening trust in the charitable sector, making Kuwait a model to be followed in dealing with humanitarian crises. The study also revealed that the challenges faced by these organizations require the development of new strategies to enhance their ability to respond to future crises. The researcher adopted the inductive analytical approach, analyzing available data and information to provide comprehensive insights into the impact of charitable organizations in Kuwait. In conclusion, the research highlights the importance of charitable work during difficult times and reflects Kuwait’s commitment to its humanitarian and social responsibilities. Keywords: Role of charitable organizations, impacts, mitigation, economic, COVID-19.